HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PENCEGAHAN PENULARAN COVID-19 DI KAMPUNG YUWANAIN KABUPATEN KEEROM - Suriyani Suriyani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
56% of all positive cases of Covid 19 in the working area of ​​the Arso Kota Health Center are in Yuwainan Village. The aim of research is knowledge and attitudes with precautions against the transmission of the Covid-19 disease in Yuwanain Village, the working area of ​​the Arso City Health Center. The research design is a quantitative study with a cross-sectional design. The research location was in Yuwanain Village, Arso District, Keerom Regency from October to November 2020. The research instrument was a questionnaire about knowledge, attitudes, and Covid-19 prevention measures. The population in this study were residents of Yuwanain Village, apart from infants, toddlers and elementary school children. 109 people. The sampling technique is total sampling. The number of samples is 109 respondents. Bivariate analysis test was made using chi square. Conclusions in this study Most of the people in Yuwanain Village had insufficient knowledge of 62 people (56.9%), sufficient attitude of 67 people (61.5%). There is a relationship between knowledge and physical distancing in efforts to prevent Covid-19 in Yuwanain Village (p=0.000). There is a relationship between knowledge and the use of masks in an effort to prevent Covid-19 in Yuwanain Village (p=0.000). There is a relationship between attitude and physical distancing in an effort to prevent Covid-19 in Yuwanain Village (p=0.001). There is a relationship between attitude and the use of masks in an effort to prevent Covid-19 in Yuwanain Village (p=0.000).